Epidemiologia das fissuras labiopalatais e avaliação fenotípica e genética da síndrome de Van der Woude - Chaves, Marcelo Reis (2006)
Clefts of the lip and/or palate account for 65% of all head and neck anomalies and can be isolated or associated with other features as part of syndromes The etiology and pathogenesis of the oral clefts particularly of the nonsyndromic origin remain poorly understood This is in part a reflection of the complexity and diversity of the molecular mechanisms involved during embryogenesis with both genetic and environmental factors playing an influential role The aim of the present study was to evaluate the occurrence of cleft lip and palate in newborns in Alfenas Minas Gerais The sample was composed by 22 cleft lip and palate patients born in Alfenas from 1986 up to 1998 (first six months) among 15,039 registered births Unilateral left cleft lip and lip-palate were more frequently found in males being the opposite in females It was also noted the highest prevalence of cleft lip-palate in males and the exclusive cleft palate in females New studies are required in other geographic areas in Brazil Van der Woude syndrome is a rare autosomal dominant disorder thought to occur with an incidence of approximately 1 in 60,000 live births and without gender predilection Van der Woude syndrome the most frequent form of syndromic clefting is characterized by the association of pits and/or sinuses of the lower lip and cleft lip and/or cleft palate This second part of this dissertation describes the clinical and genetic features of two large and unrelated families with Van der Woude syndrome in Brazil emphasizing the range of anomalies found within and between the families Van der Woude syndrome is transmitted by an autosomal dominant pattern with variable clinical expressivity high prevalence and equilibrated gender distribution Physicians should be aware of the variety of malformations which can be associated with Van der Woude syndrome Genetic counseling in Van der Woude syndrome affected families is important as a high percentage of descendants can have some kind of clefting